Use of a Multiplexed CMOS Microarray to Optimize and Compare Oligonucleotide Binding to DNA Probes Synthesized or Immobilized on Individual Electrodes - David Danley; Wanda Lyon; John Cooper; Jodi Wilmoth; Nina Yazvenko; Karl Maurer (Sensors, 2010)
The CombiMatrix microarray with 12,544 electrodes supports in situ electrochemical synthesis of user-defined DNA probes. As an alternative, we immobilized commercially synthesized DNA probes on individual electrodes coated with electropolymerized polypyrrole (Ppy). Hybridization was measured using a biotinylated target oligonucleotide and either Cy5-streptavidin and fluorescence detection or horseradish peroxidase-streptavidin and enzyme-enhanced electrochemical detection. Detection efficiencies were optimized by varying the deposition of the Ppy, the terminal groups on the DNA probes, and other factors that impacted fluorescence quenching and electrical conductivity. Optimized results were compared against those obtained using a microarray with the same DNA sequences synthesized in situ. Immobilized probes produced higher fluorescence signals, possibly by providing a greater stand off between the Cy5 on the target oligonucleotide and the quenching effects of the Ppy and the platinum electrode.